2007
DOI: 10.1073/pnas.0608635104
|View full text |Cite
|
Sign up to set email alerts
|

Extensively cross-reactive anti-HIV-1 neutralizing antibodies induced by gp140 immunization

Abstract: An immunization regimen was evaluated in rabbits consisting of the soluble, oligomeric form of envelope glycoprotein of HIV-1, strain R2 (gp140(R2)), or the surface component of the same envelope (Env), gp120(R2), in the adjuvant AS02A. The gp140(R2) was selected based on its unusual CD4-independent phenotype and the exceptionally broad neutralizing response in the infected donor. The gp140(R2) immunogen induced antibodies that achieved 50% neutralization of 48/48, and 80% neutralization of 43/46 primary strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
61
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 32 publications
0
61
1
Order By: Relevance
“…The exclusive induction of B404-like NAbs only in SIVsmH635FC-infected macaques also raises the possibility that Env from SIVsmH635FC is a highly immunogenic protein that induces antibodies against the B404 epitope. The use of Env from SIVsmH635FC for vaccination may be advantageous for the induction of broadly neutralizing antibodies, because the Env from an HIV-1-infected patient with broadly neutralizing antibodies induced cross-reactive anti-HIV-1 NAbs in an animal model (69). The Env in this vaccination study is capable of mediating CD4-independent infection.…”
Section: Discussionmentioning
confidence: 88%
“…The exclusive induction of B404-like NAbs only in SIVsmH635FC-infected macaques also raises the possibility that Env from SIVsmH635FC is a highly immunogenic protein that induces antibodies against the B404 epitope. The use of Env from SIVsmH635FC for vaccination may be advantageous for the induction of broadly neutralizing antibodies, because the Env from an HIV-1-infected patient with broadly neutralizing antibodies induced cross-reactive anti-HIV-1 NAbs in an animal model (69). The Env in this vaccination study is capable of mediating CD4-independent infection.…”
Section: Discussionmentioning
confidence: 88%
“…Antienvelope VHH may also be of use in characterizing epitopes on HIV-1 envelope proteins. Attempts to design an HIV-1 immunogen that can elicit a broadly neutralizing humoral immune response have so far failed (61), although a recent study reported that extensively cross-reactive antibodies (albeit at a low titer) were induced by immunization of rabbits with a recombinant gp140 (93). It is possible that a set of neutralizing and nonneutralizing VHH may become useful in the design of such an immunogen.…”
Section: Discussionmentioning
confidence: 99%
“…In a desire to reveal structural elements that discriminate and delineate the essence of the CD4-induced (CD4i) conformational rearrangements in the HIV envelope, we and others have investigated gp120 structures using "conditional" probes, MAbs, that specifically define epitopes associated with CD4i transitions of gp120 (33)(34)(35)(36)(37)(38)(39)(40)(41). Here we describe the analysis of gp120 with a select panel of five well-established CD4i MAbs that target the core outer domain.…”
mentioning
confidence: 99%